Frescoes of Acheiropoietos in Thessaloniki: Conservatism and Novation in Byzantine Art of the First Half of the 13th Century - Likhenko, Anastasia V. (Actual Problems of Theory and History of Art, 2021)
The frescoes in the Basilica of Acheiropoietos in Thessaloniki are located in the south aisle, above the colonnade. The ensemble represents the images of the Forty Martyrs of Sebastia, depicted full length and in medallions.The Acheiropoietos frescoes are traditionally dated after 1224, when Thessaloniki was liberated from the Latins. Another important date for the study of the ensemble is 1230, when, on the day of the Forty Martyrs, the Bulgarian Tsar Ivan II Asen defeated the Epirus ruler and emperor of Thessaloniki Theodore Komnenos Doukas. According to contemporary researchers, the frescoes in Acheiropoietos could have been ordered by Manuel Komnenos Doukas (1230—1237), the next ruler of Thessaloniki and son-in-law of Ivan II Asen.A. Xyngopoulos, the first researcher of these frescoes, singled out the hands of three artists: a master of medallions, a master of full-length figures and a master of clothes. However, such a strict separation seems practically impossible. Moreover, an analysis of the style of the frescoes shows that all the figures were painted in almost similar manner, which can be seen in the interpretation of details (the shape of the ears, collarbones, eyes, hairstyles, details of clothing, etc.)Due to the volumetric interpretation of the faces in Aheiropoietos, they are often compared with the frescoes of Mileševo and the church of Sts. Peter and Paul in Tarnovo. These three monuments represent one and the same stage in the development of style and of the search for new imagery in the 13th-century Byzantine art. In this paper we tried to trace the path of this process through the ensembles from the first decades of the 13th century in Greek and Slavic Macedonia and Bulgaria.This research has been completed with the  support of the Russian Science Foundation (RSF), project № 20-18-00294.
Keywords: Byzantine art; monumental painting of Northern Greece; art of Macedonia; art of Thessaloniki; Acheiropoietos in Thessaloniki